A Perspective on Implementation Outcomes and Strategies to Promote the Uptake of COVID-19 Vaccines - Pilar, Meagan; Elwy, A. Rani; Lushniak, Larissa; Huang, Grace; McLoughlin, Gabriella M.; Hooley, Cole; Nadesan-Reddy, Nisha; Sandler, Brittney; Moshabela, Mosa; Alonge, Olakunle; Geng, Elvin; Proctor, Enola (Frontiers in Health Services, 2022)
Recent articles have highlighted the importance of incorporating implementation science concepts into pandemic-related research. However, limited research has been documented to date regarding implementation outcomes that may be unique to COVID-19 vaccinations and how to utilize implementation strategies to address vaccine program-related implementation challenges. To address these gaps, we formed a global COVID-19 implementation workgroup of implementation scientists who met weekly for over a year to review the available literature and learn about ongoing research during the pandemic. We developed a hierarchy to prioritize the applicability of “lessons learned” from the vaccination-related implementation literature. We identified applications of existing implementation outcomes as well as identified additional implementation outcomes. We also mapped implementation strategies to those outcomes. Our efforts provide rationale for the utility of using implementation outcomes in pandemic-related research. Furthermore, we identified three additional implementation outcomes: availability, health equity, and scale-up. Results include a list of COVID-19 relevant implementation strategies mapped to the implementation outcomes.